Government Pricing Policy and Oil Palm Smallholder Income Study on Oil Palm Farmers in East Aceh - Muhammad Haykal; Iswadi Bensaadi; Saifuddin Yunus (Proceedings of Malikussaleh International Conference on Multidisciplinary Studies (MICoMS), 2022)
This study examines the influence of government pricing policies in determining the selling price of fresh fruit bunches (FFB) on the income of oil palm farmers. The research was conducted on oil palm smallholders in East Aceh who were determined based on convenience sampling. There are 100 oil palm smallholder respondents appointed to represent all oil palm smallholders in East Aceh. Data was collected using a questionnaire by taking samples of oil palm farmers in 10 districts in East Aceh. The question items are formed based on the indicators of each variable. This study was tested using multiple linear regression. The results of the study prove that the price policy issued by the government in determining cooking oil has a negative effect on the income of oil palm farmers. Palm oil farmers hope that the government's role will be more equitable in formulating price policies, so that prices tend to be stable and based on developments in world CPO prices. At present the role of the government tends to be perceived by farmers as none exist, the purchase price of FFB is mostly determined by the PKS factories in accordance with the wishes of large capital owners. There needs to be strong sanctions given to palm oil mill owners (PKS) when they tend to prioritize processing their own plantation products during large harvests compared to buying produce from community-owned oil palm planters. The results of this study provide theoretical implications about the importance of the government's role in increasing the income of oil palm farmers. Palm oil farmers need to always be accompanied by the government with regulations that not only benefit farmers but can also increase the economic growth of a region in the long term.